CCR5 polymorphisms and its relationship with HIV susceptibility, viral load and CD4 count in early antiretroviral therapy among HIV patients in Selangor and Terengganu - Mohamad Isa, Irma Izani; Abu Bakar, Suhaili; Zolraimi, Umi Rufaidah; Khairil Wahidin, Nurfhaezah; Matnor, Nur Sakinah; Othman, Zulkefley (UPM Press, 2023)
Introduction: Early studies have suggested the role of C-C chemokine receptor type 5 (CCR5) polymorphisms in influencing HIV pathogenesis and phenotypes, including the protection against HIV infection and delaying disease progression to AIDS. This study aimed to further determine the impact of CCR5 variants (CCR5-Δ32 and CCR5R223Q) on HIV susceptibility, viral load suppression and CD4 recovery during highly active antiretroviral therapy (HAART) among Malaysian HIV patients. Methods: This cross-sectional study involved 182 HIV-infected who were recruited from three out-patient clinics, and 150 non-HIV subjects from Malay, Chinese and Indian ethnicities. CD4 count and viral load data at 4-6 months (t1) and 8-12 months (t2) after starting HAART were gathered from hospital records. Chi-square test was used to analyse the correlation between CCR5 variants with dependent variables. Results: Heterozygous CCR5-Δ32 and CCR5-R223Q occurred in a percentage of 0.5% (1/182) and 1.7% (3/182) among HIV patients respectively, while none of homozygous mutant for CCR5-Δ32 and CCR5-R223Q were found. CCR5-R223Q was found more frequently in non-HIV as compared to the HIV group (P=0.018). However, both polymorphisms were not found to be correlated with CD4 recovery to ≥500 cells/mm3 (P>0.05) and viral load suppression ≤50 copies/mL (P>0.05). Conclusion: CCR5-R223Q and CCR5-Δ32 alleles probably have no modifying effects on HIV susceptibility virological and immunological recoveries in the first 12 months of HAART, partially due to the low prevalence of these mutations in the studied population.